Pengembangan Perangkat Lunak Untuk Pengukuran 2D Berbasis Citra - Triyono, Triyono; Aditya, Aditya (Program Studi Teknik Mesin, Universitas Trisakti, 2007)
Software Development for 2D Measurement Based on an Image. Theprincipal ofdigitalimage measurement program is transferring a taken image object to computer to be process to digitaldata andfrom digital data to numeric value. Digital camera and USB can be used as transferring dataequipment, and to retain the objectflatness, a measurement table is used as the based. The imageobjectthat shownin the computer monitor will be use as a guidefor the dimensional measurement by choosingthesurface target area. The dimension attain is theresult ofthe Cartesian coordinate system reading ofthe measured imageobject. The superiority ofthissoftware is the object can beplaced anywhere aroundthe measurement table. The software is made with Visual Basic language and can be usedfor objecttharare: easy to deflect, electrostatic free, small and thin.